Financial risks as one of the barriers to investment in the green economy - Zholamanova, M; Assanova, D (Journal of Economic Research & Business Administration, 2016)
The article touched upon the financial risks as one of the barriers to investment in the green economy. The article discusses the methodologi cal foundations of the impact on the level of leverage internal risk venture. The article discusses the concepts of financial risk, operational risk, the threshold of profitability. Profitability threshold – the minimum volume of sales at which a given business pays for the costs invested in it. If the volume of sales below the threshold of profitability, the company makes a loss, if the above – a profit. The article raised indicator that the entity must be considered when formulating its strategy – this financial headroom.